Oxytocin in Huntington’s disease and the spectrum of amyotrophic lateral sclerosis-frontotemporal dementia - Bergh, Sofia; Cheong, Rachel Y.; Petersén, Åsa; Gabery, Sanaz (Frontiers in Molecular Neuroscience, 2022)
Neurodegenerative disorders (NDDs) such as Huntington’s disease (HD) and the spectrum of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are characterized by progressive loss of selectively vulnerable populations of neurons. Although often associated with motor impairments, these NDDs share several commonalities in early symptoms and signs that extend beyond motor dysfunction. These include impairments in social cognition and psychiatric symptoms. Oxytocin (OXT) is a neuropeptide known to play a pivotal role in the regulation of social cognition as well as in emotional behaviors such as anxiety and depression. Here, we present an overview of key results implicating OXT in the pathology of HD, ALS and FTD and seek to identify commonalities across these NDDs. OXT is produced in the hypothalamus, a region in the brain that during the past decade has been shown to be affected in HD, ALS, and FTD. Several studies using human post-mortem neuropathological analyses, measurements of cerebrospinal fluid, experimental treatments with OXT as well as genetic animal models have collectively implicated an important role of central OXT in the development of altered social cognition and psychiatric features across these diseases. Understanding central OXT signaling may unveil the underlying mechanisms of early signs of the social cognitive impairment and the psychiatric features in NDDs. It is therefore possible that OXT might have potential therapeutic value for early disease intervention and better symptomatic treatment in NDDs.